Pemanfaatan Media Animasi Dalam Meningkatkan Literasi Menabung pada Siswa Madrasah Ibtidaiyyah Maslakul Falah Klaling Kudus - Amaroh, Siti; Murtaja, Rohit; Saputri, Virgie Eka; Budiansyah, Ahmad Samudra Alan; Masturin, Masturin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
Early financial literacy plays a crucial role in fostering rational and responsible financial attitudes and behaviors. Nevertheless, the delivery of saving literacy materials for Madrasah Ibtidaiyyah students often faces challenges due to the use of instructional methods that are less engaging and not fully aligned with the characteristics of the alpha generation. This community service program aims to improve students’ savings literacy through the use of animated media at Madrasah Ibtidaiyyah Swasta Maslakul Falah Klaling Kudus. The program employed an interactive approach supported by contextually designed animated videos. The implementation was conducted through systematic stages, including planning, preparation, implementation, and evaluation, with fourth-grade students as the target participants. The findings indicate that the use of animated media effectively enhanced students’ learning engagement, comprehension, and active participation in understanding fundamental financial literacy concepts, such as the function of money, distinguishing between needs and wants, the benefits of saving, and the establishment of simple financial goals. Animated media proved to be an effective educational tool that aligns with the digital-oriented characteristics of Madrasah Ibtidaiyyah students. This program is expected to serve as an alternative model for delivering financial literacy education that is both effective and engaging at the primary education level .